Psychopathology of Young Terrorist Offenders, and the Interaction With Ideology and Grievances - Duits, Nils; Alberda, Daphne L.; Kempes, Maaike (Frontiers in Psychiatry, 2022)
Psychopathology is considered a risk factor for interpersonal violence in adult and young offenders. Some mental disorders are possibly more prevalent in adult lone actor terrorist offenders. The prevalence of psychopathology in young terrorist offenders is not known, nor whether and how it relates to ideological beliefs and grievances and anger about perceived injustice. Therefore, we examined whether psychopathology is present in 51 young terrorist offenders and to what extent psychopathology is related to supporting a violent ideology, and grievances and anger about perceived injustice. We examined whether this differs from 140 adult terrorist offenders. We made use of primary source judicial information and forensic mental health reports. Most young terrorist offenders with a forensic mental health assessment had psychopathological problems. Most frequently found mental disorders in young terrorist offenders were intellectual disability, psychotic/schizophrenic disorders, and cluster B personality disorders. Most frequently found traits and symptoms of mental disorders were problems with relationships, poor regulation of aggression, cluster B personality traits, depressive symptoms, psychotic/schizophrenic symptoms, feelings of anger, paranoid feelings, substance use symptoms, and cluster A and C personality traits. Young terrorist offenders more often showed poor regulation of aggression than older terrorists. In addition, our results showed the first indications for the interrelatedness of psychopathology and violent ideology, grievances, and the anger about perceived injustice in young and older terrorist offenders. This stresses the importance to include psychopathology in risk assessment instruments such as the VERA-2R and of future research on psychopathology in combination with personal and contextual risk factors in terrorist offenders.